2020
DOI: 10.1038/s41598-020-66327-9
|View full text |Cite
|
Sign up to set email alerts
|

Acellular bioscaffolds redirect cardiac fibroblasts and promote functional tissue repair in rodents and humans with myocardial injury

Abstract: Coronary heart disease is a leading cause of death. Tissue remodeling and fibrosis results in cardiac pump dysfunction and ischemic heart failure. Cardiac fibroblasts may rebuild damaged tissues when prompted by suitable environmental cues. Here, we use acellular biologic extracellular matrix scaffolds (bioscaffolds) to stimulate pathways of muscle repair and restore tissue function. We show that acellular bioscaffolds with bioinductive properties can redirect cardiac fibroblasts to rebuild microvascular netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…Decellularized tissues were readily translated into the clinic as surgical scaffolds since ECM molecules are highly preserved across species, permitting the application of allogenic and xenogenic tissue-derived ECM. These applications demonstrated low immunogenicity while promoting specific cell functions ( Wicha et al, 1982 ; Badylak, 2004 ; Gilbert et al, 2006 ; Crapo et al, 2011 ; Svystonyuk et al, 2020 ). Decellularization methodologies have evolved toward whole-organ decellularization by improvements such as the delivery of decellularization agents through the vasculature (perfusion) which promotes clearance of cellular remnants in situ ( Ott et al, 2008 ; Badylak et al, 2011 ).…”
Section: Ecm Modulationmentioning
confidence: 99%
“…Decellularized tissues were readily translated into the clinic as surgical scaffolds since ECM molecules are highly preserved across species, permitting the application of allogenic and xenogenic tissue-derived ECM. These applications demonstrated low immunogenicity while promoting specific cell functions ( Wicha et al, 1982 ; Badylak, 2004 ; Gilbert et al, 2006 ; Crapo et al, 2011 ; Svystonyuk et al, 2020 ). Decellularization methodologies have evolved toward whole-organ decellularization by improvements such as the delivery of decellularization agents through the vasculature (perfusion) which promotes clearance of cellular remnants in situ ( Ott et al, 2008 ; Badylak et al, 2011 ).…”
Section: Ecm Modulationmentioning
confidence: 99%
“…Data from preclinical and clinical evaluation of acellular biologic ECM scaffolds in cardiac pump dysfunction and ischemic heart failure showed reduced fibrotic tissue, improved perfusion of infarcted myocardium, and reverse structural remodeling [ 66 ]. A decellularized pericardial matrix colonized with human viable Wharton’s jelly-derived mesenchymal stromal cells was implanted in patients with non-revascularizable myocardial scars and has shown a reduction in scar mass after three months [ 67 ].…”
Section: Decellularized Extracellular Matricesmentioning
confidence: 99%
“…Similar to tetrandrine, his group has also demonstrated that the SGLT2 inhibitor empagliflozin converted myofibroblasts into a more quiescent phenotype, inhibiting ECM remodelling and attenuating pro-fibrotic marker expression [ 113 ]. His recent work with acellular bioactive scaffolds has shown that implanting them into the heart in a rat MI model, as well as in humans, can redirect cardiac fibroblasts from a fibrotic to a vasculogenic nature, resulting in improved cardiac function, inhibition of post-MI cardiac remodelling, and improving perfusion of the infarcted heart, providing a tractable clinical means to improve cardiac repair during surgical re-vascularization procedures [ 114 ].…”
Section: Canadian Contributions To Understanding Fibroblast Biologymentioning
confidence: 99%